The Model of Business Tourism in Area of Eastern Economic Corridor (EEC) - Sermsomboon, Khemmaratt; Jaroenwisan, Kaedsiri (Journal of Liberal Arts and Management Science Kasetsart University, 2022)
This article is to inform investors and entrepreneurs about the business tourism strategy for the Eastern Economic Corridor (EEC) by identifying features of tourists capable of segmenting the business tourist market and defining marketing objectives. According to the survey, MICE enterprises, also the development and promotion of tourism in order to transform the Eastern Economic Corridor’s tourist industry into one of world-class sustainability are the most significant tourist types that create the majority of the region's revenue. Government agencies have made investments in the large auditorium business, the International Exhibition Center, and health-oriented tourism development to support quality tourists, as well as investments in infrastructure and logistics development for the eastern region to support Bangkok's growth, such as the high-speed rail project connecting three airports and the double-track railway development of U-Tapao Airport, etcetera. In addition, in support of promoting business tourism to specific populations, Plans call for the development of tourism sites and infrastructure to serve Bleisure visitors, who, according to the survey, are millennials. This group's conduct has a significant impact on the demand and supply of the tourism sector, particularly corporate tourism.